A utilização de créditos de carbono no Brasil: uma visão econômica e financeira - Said, Acef Antonio (2007)
The present work analyses the impact of the carbon trading market on the national economy, evaluating its influence on the Gross Domestic Product of Brazil, and proposes actions to foster carbon trading in the country. The study traces the historic evolution of United Nations (UN) environmental conventions, and analyses UN’s main environmental programs. Special attention is given to the Kyoto Protocol, which created the Clean Development Mechanism, CDM, and, therefore, carbon trading and the “environmental currency” Certified Emission Reductions. The relationship between carbon trading, scientific research, agribusiness, and the formation of public and private parks, is analyzed and actions relevant to the environmental and economic development of Brazil are proposed. The work also presents statistics of brazilian CDM projects presented until January of 2007, and information on the formatting of CDM projects, based on three projects approved by UN’s Executive Council. Finally, the work describes ITAPAR, a non-governmental organization created by the author devoted to environmental causes in Paraná and Brazil